Enhancement of photosynthesis efficiency and yield of strawberry (Fragaria ananassa Duch.) plants via LED systems - Guiamba, Helio Dos Santos Suzana; Zhang, Xiwen; Sierka, Edyta; Lin, Kui; Ali, Muhammad Moaaz; Ali, Waleed M.; Lamlom, Sobhi F.; Kalaji, Hazem M.; Telesiński, Arkadiusz; Yousef, Ahmed Fathy; Xu, Yong (Frontiers in Plant Science, 2022)
Due to advances in the industrial development of light-emitting diodes (LEDs), much research has been conducted in recent years to get a better understanding of how plants respond to these light sources. This study investigated the effects of different LED-based light regimes on strawberry plant development and performance. The photosynthetic pigment content, biochemical constituents, and growth characteristics of strawberry plants were investigated using a combination of different light intensities (150, 200, and 250 μmol m−2 s−1), qualities (red, green, and blue LEDs), and photoperiods (14/10 h, 16/8 h, and 12/12 h light/dark cycles) compared to the same treatment with white fluorescent light. Plant height, root length, shoot fresh and dry weight, chlorophyll a, total chlorophyll/carotenoid content, and most plant yield parameters were highest when illuminated with LM7 [intensity (250 μmol m−2 s−1) + quality (70% red/30% blue LED light combination) + photoperiod (16/8 h light/dark cycles)]. The best results for the effective quantum yield of PSII photochemistry Y(II), photochemical quenching coefficient (qP), and electron transport ratio (ETR) were obtained with LM8 illumination [intensity (250 μmol m−2 s−1) + quality (50% red/20% green/30% blue LED light combination) + photoperiod (12 h/12 h light/dark cycles)]. We conclude that strawberry plants require prolonged and high light intensities with a high red-light component for maximum performance and biomass production.